Exploring Religiosity and Psychological Well-being in Security Guards: An Empirical Analysis - Wahyuni, Siti Fujia; Mariyati, Lely (Indonesian Journal of Islamic Studies, 2023)
This quantitative correlation study investigates the relationship between religiosity (independent variable) and psychological well-being (dependent variable) among 243 security guards at a private security firm. Employing a simple random sampling technique, data was collected using standardized scales measuring religiosity and psychological well-being. The analysis yielded a correlation coefficient (rxy) of 0.073 with a significance value (p) of 0.208 (> 0.05), indicating a non-significant relationship between religiosity and psychological well-being in this specific occupational group. These findings offer valuable insights into the complex interplay between religiosity and psychological well-being among security guards, shedding light on potential avenues for further research and interventions aimed at enhancing the well-being of this workforce. Highlights: Limited Correlation: The study reveals a minimal and non-significant correlation (rxy = 0.073) between religiosity and psychological well-being among security guards. Occupational Context: It focuses on the specific occupational context of security guards, shedding light on their unique well-being challenges. Research Implications: The findings provide a basis for further research and interventions to improve the well-being of security personnel. Keywords: Religiosity, Psychological well-being, Security guards, Quantitative correlation, Occupational well-being